The Tendency of Transition from Structural to Functional Positions in National Civil Service Agency and the Ministry of Environment and Forestry - Amy Yayuk Sri Rahayu; Krisna Puji Rahmayanti (Indonesian Association for Public Administration, 2018)
This study aims to highlight the phenomenon of transition from structural to functional positions in government bureaucracy in Indonesia. Since in this modern era, an environmental change strongly influences public organizations which encourage public organizations like bureaucracy must be adaptive. In line with the issuance of Law No. 5/2014 on State Civil Apparatus (ASN), public organizations such as bureaucracy have undergone reform to be structurally lean and functionally rich. Consequently, there is a gradual change that government institutions change from structural to functional positions. The methodology applied is post-positivism. The concept of job analysis in the structure of public organizations is deductively downgraded into its indicators and then used as guidance in qualitative data collection. The result found that, firstly, job analysis is still applied and relevant to determine Administrative and Functional Positions in both government institutions, yet it is not carried out systematically and optimally. Secondly, the trend in the tendency of transition from structural to functional positions in both government institutions is due to the misperception of the employees towards Functional Positions.